A New Hamiltonian Chaotic System with Coexisting Chaotic Orbits and its Dynamical Analysis - Vaidyanathan, Sundarapandian; Sambas, Aceng; Zhang, Sen; Mohamed, Mohamad Afendee; Mamat, Mustafa (International Journal of Engineering and Technology, 2018)
Hamiltonian chaotic systems are conservative chaotic systems which arise in many applications in Classical Mechanics. A famous Hamiltonian chaotic system is the H´enon-Heiles system (1964), which was modeled by H´enon and Heiles, describing the nonlinear motion of a star around a galactic centre with the motion restricted to a plane. In this research work, by modifying the dynamics of the H´enon-Heiles system (1964), we obtain a new Hamiltonian chaotic system with coexisting chaotic orbits. We describe the dynamical properties of the new Hamiltonian chaotic system.